Evaluation of E-Government Implementation in Managing Public Service Complaints Using E-GovQual and Importance Performance Analysis (Case Study: CRM - Cepat Respon Masyarakat – of the Jakarta Provincial Government) - Sabri Alim; Habibullah Akbar; Gerry Firmansyah; Nenden Siti Fatonah; Budi Tjahjono (Universitas Raharja, 2024)
The improvement of public service quality is an effort to enhance the quality and innovation of public services within each government agency periodically, according to the needs and expectations of the society. One of the efforts to enhance the quality of service by public service providers, in order to improve the well-being of the community, is to use public complaints as a basis for making improvements in public services. According to data from the Central Bureau of Statistics in 2022, the population of DKI Jakarta is 10,679,000. The Provincial Government of DKI Jakarta has an integrated complaint system called